State Policies and Women's Autonomy in China, India, and the Republic of Korea, 1950-2000 : Lessons from Contrasting Experiences - Das Gupta, Monica; Lee, Sunhwa; Uberoi, Patricia; Wang, Danning; Wang, Lihong; Zhang, Xiaodan (World Bank, Washington, DC, 2014)
The authors compare changes in gender roles and women's empowerment in China, India, and the Republic of Korea. Around 1950, these newly formed states were largely poor and agrarian, with common cultural factors that placed similar severe constraints on women's autonomy. They adopted very different paths of development, which are well known to have profoundly affected development outcomes. These choices have also had a tremendous impact on gender outcomes, and today these countries show striking differences in the extent of gender equity achieved. China has achieved the most gender equity, the Republic of Korea the least. The authors conclude that: a) States can exert enormous influence over gender equity. They can mitigate cultural constraints on women's autonomy (as in China and India) or slow the pace of change in gender equity despite women's rapid integration into education, formal employment, and urbanization (as in the Republic of Korea). b) The impact of policies to provide opportunities for women's empowerment can be greatly enhanced if accompanied by communication efforts to alter cultural values that place heavy constraints on women's access to those opportunities.